Is Milan for kids?: The Milan System for Reporting Salivary Gland Cytology in pediatric patients at an academic children's hospital with cytologic‐histologic correlation. Issue 11 (2nd June 2021) - Satturwar, Swati P.; Fuller, Maren Y.; Monaco, Sara E.
Abstract : Background: The Milan System for Reporting Salivary Gland Cytopathology (MSRSGC) provides a useful framework for the diagnosis of salivary gland fine‐needle aspiration (FNA) biopsies. In this study, the MSRSGC was applied to salivary gland FNAs in pediatric patients to assess its usefulness and look at pitfalls. Methods: The laboratory information system was queried over a 15‐year period for all salivary gland FNAs in patients 18 years old or younger. Patient demographics, FNA diagnosis categorized according to the MSRSGC, and follow‐up surgical pathology diagnoses were examined and correlated. Results: Thirty‐two cases were identified, with an average age of 12 years (range, 0.6‐18 years). A majority of the cases (84.4%) were from the parotid region. Twenty of 32 cases (62.5%) had follow‐up resection. MSRSGC recategorization diagnoses of the 32 FNA cases were 34% benign neoplasm, 31% nonneoplastic, 16% nondiagnostic, 9% atypia of undetermined significance, 3% salivary neoplasm of uncertain malignant potential, 3% suspicious for malignancy, and 3% malignant. Overall, the sensitivity and specificity were 100% and 80%, respectively. On follow‐up resection, 55% were neoplastic: pleomorphic adenomas (n = 6; 55%), pilomatricoma (n = 3; 28%), mucoepidermoid carcinoma (n = 1; 9%), schwannoma (n = 1; 9%), and myofibroma (n = 1; 9%). Conclusions: The MSRSGC performed fairly well in the pediatric population with a low overall risk of malignancy (6%) and high sensitivity. Although the majority of pediatric salivary gland FNAs were benign, 55% of resected cases were positive for a neoplasm, with benign neoplasms outnumbering malignancy. Challenging entities included inflammatory conditions, like immunoglobulin G4‐related sialadenitis, and skin and soft tissue lesions near the salivary gland. Abstract : The usefulness of the newly introduced Milan system for reporting salivary gland cytology has been studied for adult patients in only a few institutions. Our study, which evaluated the usefulness of the Milan system for pediatric patients at an academic children's hospital, showed high sensitivity for the detection of salivary gland neoplasms/lesions in kids with overall low malignancy rates and highlighted morphological pitfalls through a detailed cytologic‐histologic correlation.